Judicial Mechanisms for the Implementation of Transitional Justice at National and International Levels - Ayoub, Rehan Hanna; al-Huseini, Malik Mansi (Journal of Posthumanism, 2025)
Judicial mechanisms are one of the main tools in implementing transitional justice domestically, seeking to pursue accountability and reparations for victims through the prosecution of perpetrators of violations of gross human rights. Such mechanisms can be national courts specifically constituted or set up to hear these cases, or can include hybrid panels involving national and international judges for ensuring integrity and transparency. They strive to secure the rule of law, bring about the truth, and put an end to repetitions of the abuse, as appropriate to a fair trial standard and protecting the accused's rights as well as the victims. Success for such mechanisms depends on independence of the judiciary, appropriation of adequate resources therefor, and commitment on the part of the state to seriously and equitably deal with the past.